2016
DOI: 10.1007/978-3-319-46922-5_12
|View full text |Cite
|
Sign up to set email alerts
|

A Weighted K-AP Query Method for RSSI Based Indoor Positioning

Abstract: Abstract. The paper studies the establishment of offline fingerprint library based on RSSI (Received Signal Strength Indication), and proposes WF-SKL algorithm by introducing the correlation between RSSIs. The correlations can be transformed as AP fingerprint sequence to build the offline fingerprint library. To eliminate the positioning error caused by instable RSSI value, WF-SKL can filter the noise AP via online AP selection, meanwhile it also reduces the computation load. WF-SKL utilizes LCS algorithm to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…By contrast, MUSIC algorithms are much complex, and the complexities of the standard MUSIC 27 and low complexitymultiple signal classification (LC-MUSIC) 29 are computed as 2.57 3 10 6 and 3.16 3 10 5 floatingpoint operations per second, respectively. For fingerprint-based localization algorithm, fingerprint data are stored in a database on the computer, for example, WF-SKL algorithm 19 uses a computer installed the MySQL database for data analyzing and the positioning speed is lower than 0.5 s for a fingerprint distance of 5 m. Although localization with dynamic channel allocation (LDCA) algorithm 32 is clean and efficient as it requires one addition, one division, and one involution, four sectors in the anchor node work separately on different channels, therefore only distance could be estimated for RSSI lookup table. In a word, system memory and processor capability requirements are limited for our algorithm, and this algorithm could be easily realized in most WSN-embedded systems.…”
Section: Algorithm Complexity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, MUSIC algorithms are much complex, and the complexities of the standard MUSIC 27 and low complexitymultiple signal classification (LC-MUSIC) 29 are computed as 2.57 3 10 6 and 3.16 3 10 5 floatingpoint operations per second, respectively. For fingerprint-based localization algorithm, fingerprint data are stored in a database on the computer, for example, WF-SKL algorithm 19 uses a computer installed the MySQL database for data analyzing and the positioning speed is lower than 0.5 s for a fingerprint distance of 5 m. Although localization with dynamic channel allocation (LDCA) algorithm 32 is clean and efficient as it requires one addition, one division, and one involution, four sectors in the anchor node work separately on different channels, therefore only distance could be estimated for RSSI lookup table. In a word, system memory and processor capability requirements are limited for our algorithm, and this algorithm could be easily realized in most WSN-embedded systems.…”
Section: Algorithm Complexity Analysismentioning
confidence: 99%
“…Although a building signal strength distribution map could be helpful in high-accuracy positioning, experiments showed that environment parameters and radio signal change would affect positioning results significantly. 18 Recently, Huo et al 19 presented a fingerprint-based localization algorithm called a weighted K-AP query method for RSSI based indoor positioning (WF-SKL). Large-scale positioning experiments indicated that the algorithm is effective and accurate.…”
Section: Introductionmentioning
confidence: 99%